QUALITY OF LIFE, PHYSICAL ACTIVITY AND COGNITION IN THE ELDERLY POPULATION: A SYSTEMATIC REVIEW - Nazar, Fabiano; Gomes, Fabio Ricardo Hilgenberg; de Oliveira, Valdomiro; Vagetti, Gislaine Cristina (Uningá Review, 2020)
The presents studies verification the perform a review on the theme "quality of life, physical activity and cognition in the elderly population". The search for studies occurred in seven databases and in the list of references of the selected articles. The original studies, published between 2005 and 2017, that investigated the association or relationship between quality of life (QOL), physical activity (PA) and cognition, or those that had as outcome some of these variables included in the review, and studied individuals older adults. We found 544 potentially relevant titles; 16 of them met the inclusion criteria and were reviewed. These included four intervention studies, a prospective cohort study, and eleven cross-sectional studies. Of the total research, 87.5% involved elderly people of both sexes. QOL was largely related to the fact that they were physically active and cognition was associated with FA and good perception of QOL. Education appeared in most studies as sociodemographic data and only one study applied it as intervention. Evidence on the impact of frequency and intensity of PA on aspects of QOL and cognition is still limited. Longitudinal and interventional studies are needed to better understand this dose / response relationship between AF, QOL and cognition. The association between AF, QOL and cognition is more complex than is generally reported in the literature and seems to involve more mediating variables.